Analysis of Normal and Epileptic EEG Signals with Filtering Methods - Gur, Duygu; Kaya, Turgay; Turk, Mustafa (Ieee, 2014)
EEG signals taken from brain surface have low amplitude and low frequency band and are nonstationary biological signals. The other electrical signals in the environment and originated from the voluntary-involuntary movements of the person may cause additional noise. So EEG records, like other biological signals, requires accurate measurement. In this study, normal/ epileptic EEG signals in relating to the WAG / Rij rats, high frequency and low frequency noise were suppressed by moving average filter and derivative-based filter, respectively. Then, the frequency spectrum of the signals were presented. Thus, it was aimed to diagnose illness by comparing the frequency band of signals concentrated intended.
Normal ve epileptik EEG sinyallerinin filtreleme yöntemleri ile analizi
22nd IEEE Signal Processing and Communications Applications Conference (SIU) -- APR 23-25, 2014 -- Karadeniz Teknik Univ, Trabzon, TURKEY
Keywords: EEG; epilepsy; fourier transform; derivative based filter; moving avaraged filter